Cunila socorroae (Lamiaceae) a new species from Sierra Madre Occidental, Durango, Mexico - García-Peña, María Del Rosario; González-Gallegos, Jesús Guadalupe (Phytotaxa, 2020)
Recent botanical explorations in Durango, Mexico, led to the discovery of a new species endemic to this state: Cunila socorroae (Lamiaceae), which is consequently here described and illustrated. The new species is morphologically most similar to C. jaliscana and C. lythrifolia. It can be distinguished from both in having less flowers per cyme, lanceolate floral bracts, longer calyx tube, and lanceolate calyx teeth and longer. It also deviates from C. jaliscana by the fewer floral internodes, longer floral bract, and generally longer corolla tube. Also, the exfoliating bark, white corollas and internally pubescent, make a clear distinction against C. lythrifolia. The distinctive geographic distribution of these species is an additional support to their separation; the new species is exclusive of the middle portion of Sierra Madre Occidental, whereas C. jaliscana is restricted to the northernmost portion of Sierra Madre del Sur, and C. lythrifolia, though mostly occurs in eastern Tans-Mexican Volcanic Belt, has also some localities in southern Chihuahuan Desert, Sierra Madre Oriental and Sierra Madre del Sur.